KNOWLEDGE AND ATTITUDE OF SELF-MEDICATION AMONG HEALTHCARE AND NON-HEALTHCARE STUDENTS OF LAHORE, PAKISTAN - Shahid, Sara; Ahmed, Fahad; Khan, Rabeel; Bajwa, Amna; Sana, Anosh; Ibtsam, Muhammad; Iqbal, Muhammad Zahid (Universal Journal of Pharmaceutical Research, 2023)
Introduction: Self-medication is regarded as the system of taking medicines without the consultation of licensed medical practitioner. Self-medication leads to irrational use of medical drugs which is hazardous for health. The prevalence of this crucial issue is rapidly increasing worldwide. The present study was aimed to access the pattern of self-medication trends in healthcare students and non-healthcare students of Lahore, Pakistan. Methods: A cross-sectional survey based observational study has been conducted to access the knowledge along with the attitude of medical and non-medical students regarding self-medication. The study settings included different universities and medical colleges of Lahore, Pakistan. A total of 301 students from medical department and other departments were included in the study. A validated self-medication assessment questionnaire was used to access the knowledge along with attitude pattern of self-medication among healthcare students as well as non-healthcare students. Results: The findings of the present study presented that medical students are more aware of the potential side effects and adverse reactions of the self-medicated drug as compared to the non-medical students. Whereas, trends of self-medication was observed to be slightly higher in healthcare students as compared to the non-healthcare students. Moreover, the frequency of antibiotic use was comparatively more frequent in medical students as compared to the non-medical graduates. Whereas, the use of painkillers without prescription was more prevalent in non-medical students as compare to the medical graduates. Conclusion: There has been a significant difference in knowledge of healthcare students and non-healthcare students of Lahore, Pakistan. Although both healthcare and non-healthcare students have high prevalence of self-medication but differences have been observed in case of drugs taken. Healthcare students practice self-medication more as compared to the non-health-care students. Peer Review History: Received: 6 October 2022; Revised: 11 November; Accepted: 27 December 2022, Available online: 15 January 2023 Academic Editor: Dr. Asia Selman Abdullah , Pharmacy institute, University of Basrah, Iraq, asia_abdullah65@yahoo.com Reviewers: Dr. A.A. Mgbahurike, University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Prof. Hassan A.H. Al-Shamahy, Sana’a University, Yemen, shmahe@yemen.net.ye